Taxonomy of protoplanetary discs observed with ALMA. Issue 2 (3rd February 2022) - Parker, Raeesa; Ward-Thompson, Derek; Kirk, Jason
ABSTRACT: Many observations of protoplanetary discs studied with ALMA have revealed the complex substructure present in the discs. Rings and gaps in the dust continuum are now a common sight in many discs; however, their origins still remain unknown. We look at all protoplanetary disc images taken with ALMA from cycles 0 to 5 and find that 56 discs show clear substructure. We further study the 56 discs and classify the morphology seen according to four categories: Rim, Ring, Horseshoe, and Spiral. We calculate the ages of the host stars using stellar isochrones and investigate the relation between the morphology of the substructure seen in the protoplanetary discs and the age of the host stars. We find that there is no clear evolutionary sequence in the protoplanetary discs as the stars increase in age, although there is a slight tendency for spirals to appear in younger systems and horseshoes to be seen in more evolved systems. We also show that majority of the images of protoplanetary discs made by ALMA may not have had a sufficiently high resolution or sensitivity to resolve substructure in the disc. We show that angular resolution is important in detecting substructure within protoplanetary discs, with sensitivity distinguishing between the different types of substructure. We compare the substructure seen in protoplanetary discs at sub-mm to those seen in scattered light. We find that cavities are a common substructure seen in discs at both sub-mm wavelengths and in scattered light.